2015
DOI: 10.1007/s40333-015-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

The ecological role of dew in assisting seed germination of the annual desert plant species in a desert environment, northwestern China

Abstract: It is important to understand the effects of dew events on non-mucilaginous seed germination of annual desert plant species during dry seasons, which is critical to maintaining long-term soil seed banks in a harsh desert environment. We hypothesize that dew deposition also assists in the non-mucilaginous seed germination of annual desert species. A common field dew treatment experiment was conducted in the Linze Inland River Basin Research Station to investigate the effects of dew deposition on the seed germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Among the positive roles played by dew and fog are also an increase in the relative water content of the leaves (Gouvre & Grammatikopoulos, 2003), branches (Hill et al, 2015;Yates & Hutley, 1995), and the xylem water potential (Berry & Smith, 2013;Kim & Lee, 2011), all of which assist in chlorophyll and carotenoid recovery . Additionally, dew and fog may reduce wilting and increase survival probabilities during water stress (Babu & Went, 1978;Cosh et al, 2009;Duvdevani, 1957), improve the recovery of DNA damage of seeds (Gutterman & Shem-Tov, 1997;Yang, Zhang, Dong, Boubriak, & Huang, 2011;Zhuang & Zhao, 2016) and germination (Yang et al, 2011;Yang, Bu, Mu, Shao, & Zhang, 2014;Zhuang & Zhao, 2016), and increase plant growth, yield, and biomass (Boucher et al, 1995;Duvdevani, 1957;Duvdevani, Reichert, & Palti, 1946;Zhuang & Ratcliffe, 2012). Although some researchers report on dew utilization by roots (Pan et al, 2010) or on the use of vapour absorption by roots (Kosmas et al, 2001;Ramírez, Bellot, Domingo, & Blasco, 2007), these claims were not yet substantiated and require further research.…”
Section: The Effects Of Nrw On Plants Snails and Insectsmentioning
confidence: 99%
“…Among the positive roles played by dew and fog are also an increase in the relative water content of the leaves (Gouvre & Grammatikopoulos, 2003), branches (Hill et al, 2015;Yates & Hutley, 1995), and the xylem water potential (Berry & Smith, 2013;Kim & Lee, 2011), all of which assist in chlorophyll and carotenoid recovery . Additionally, dew and fog may reduce wilting and increase survival probabilities during water stress (Babu & Went, 1978;Cosh et al, 2009;Duvdevani, 1957), improve the recovery of DNA damage of seeds (Gutterman & Shem-Tov, 1997;Yang, Zhang, Dong, Boubriak, & Huang, 2011;Zhuang & Zhao, 2016) and germination (Yang et al, 2011;Yang, Bu, Mu, Shao, & Zhang, 2014;Zhuang & Zhao, 2016), and increase plant growth, yield, and biomass (Boucher et al, 1995;Duvdevani, 1957;Duvdevani, Reichert, & Palti, 1946;Zhuang & Ratcliffe, 2012). Although some researchers report on dew utilization by roots (Pan et al, 2010) or on the use of vapour absorption by roots (Kosmas et al, 2001;Ramírez, Bellot, Domingo, & Blasco, 2007), these claims were not yet substantiated and require further research.…”
Section: The Effects Of Nrw On Plants Snails and Insectsmentioning
confidence: 99%
“…These results suggested that dew affected the demographic traits of L. semiglabra . Additionally, in order to utilise the sustainable water resources, most of ephemeral plants germinated in the snow melting period in spring in arid desert (Mckenna & Houle, ; Zhuang & Zhao, ). Due to the continuous water consumption by evaporation and plant absorption, the amount of snow meltwater decreased gradually along the plant growth season (Hill et al, ; Mao & Zhang, ; Steyn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dew, as an important input of water resources in a desert area, is condensed water of air moisture generated in near‐surface air at the temperature lower than the dew point temperature (Fischer, Veste, Bens, & Hüttl, ; Jacobs, Heusinkveld, & Berkowicz, ; Mchugh et al, ; Tomaszkiewicz, Najm, Beysens, Alameddine, & Elfadel, ). Therefore, the amount of dew has been anticipated to affect several ecological processes and functions including dune stability, biological soil crust, seed germination, plant survival, and biodiversity (Ben‐Asher, Alpert, & Ben‐Zvi, ; Hanisch, Lohrey, & Buerkert, ; Hill et al, ; Ratcliffe, ; Tomaszkiewicz et al, ; Zhuang & Zhao, ). However, our understandings whether and how amounts of dew affect variations in functional traits and demographic traits, which are potential indicators or factors for biodiversity and life history of a plant, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations